2018
DOI: 10.1186/s12966-018-0672-6
|View full text |Cite
|
Sign up to set email alerts
|

Sustained impact of energy-dense TV and online food advertising on children’s dietary intake: a within-subject, randomised, crossover, counter-balanced trial

Abstract: BackgroundPolicies restricting children’s exposure to unhealthy food marketing have been impeded by the lack of evidence showing a direct link between food advertising exposure and children’s energy intake and body weight. Food advertising exposure increases children’s immediate food consumption, but whether this increased intake is compensated for at later eating occasions is not known; consequently the sustained effect on diets remains unclear.MethodsWe conducted a within-subject, randomised, crossover, coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 52 publications
(2 reference statements)
2
94
0
4
Order By: Relevance
“…Children's additional kcal intake in response to acute food-marketing exposure is not compensated for at later eating occasions, and so marketing-driven overconsumption would, in time, lead to weight gain. 18 This study had some limitations. First, all children were exposed to the same 2 influencers, and individual differences that may have moderated endorser effects, such as perceived similarity, familiarity, and likeability, 58 could not be considered.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Children's additional kcal intake in response to acute food-marketing exposure is not compensated for at later eating occasions, and so marketing-driven overconsumption would, in time, lead to weight gain. 18 This study had some limitations. First, all children were exposed to the same 2 influencers, and individual differences that may have moderated endorser effects, such as perceived similarity, familiarity, and likeability, 58 could not be considered.…”
Section: Discussionmentioning
confidence: 92%
“…The Internet is now a major platform for food marketing, 15 and recent studies suggest that digital marketing may have similar effects to that of television. [15][16][17][18][19] Research has also demonstrated a "beyond-brand" effect of digital food marketing whereby irrespective of the healthfulness of a cue, children's subsequent overall food intake increases. 20,21 Children's digital media (online content) consumption is growing rapidly.…”
mentioning
confidence: 99%
“…The literature indicates that when children consume a greater amount of snack food following acute food advertising exposure (via both TV and the Internet), this additional intake is not compensated for at a later lunch meal. 58 Cohort studies indicate that an energy gap of 69 to 77 kcal per day is all that is required for a child to become overweight. 59 In the current study, children exposed to influencer food marketing with an advertising disclosure consumed 41% kcal more of the marketed snack compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…Data from healthy food adverts and no advergame control data were excluded; data for advergames with food adverts/nonfood adverts with a protective message intervention were excluded . Data for combined media (the effect of TV adverts with advergame) were excluded since the effect was inconsistent for TV or advergame analyses …”
Section: Methodsmentioning
confidence: 99%